Respuesta :
h(x) = 3x - 1
j(x) = -2x
h[j(2)] ⇒ j(2) = -2(2) ⇒ j(2) = -4
h(-4) = 3(-4) - 1
h(-4) = -12 - 1
h(-4) = -13
h[j(2)] = -13
j(x) = -2x
h[j(2)] ⇒ j(2) = -2(2) ⇒ j(2) = -4
h(-4) = 3(-4) - 1
h(-4) = -12 - 1
h(-4) = -13
h[j(2)] = -13
Answer:
Option 3rd is correct.
the value of h[j(2)] is, -13
Step-by-step explanation:
Given the functions:
[tex]h(x) = 3x-1[/tex]
[tex]j(x) = -2x[/tex]
We have to find the value of h[j(2)]
[tex]h[j(x)] = h[-2x][/tex]
Replace x from -2x in h(x) we have;
[tex]h[-2x] = 3(-2x)-1 = -6x -1[/tex]
⇒[tex]h[j(x)] = -6x-1[/tex]
Substitute the value of x = 2 we get;
[tex]h[j(2)] = -6(2)-1 = -12-1 = -13[/tex]
Therefore, the value of h[j(2)] is, -13